2022
DOI: 10.29103/jak.v10i1.6611
|View full text |Cite
|
Sign up to set email alerts
|

Urgensi Program Pengungkapan Sukarela (Tax Amnesty Jilid II) Berdasarkan Sudut Pandang Wajib Pajak

Abstract: The purpose of this study is to examine and analyze the effect of the Voluntary Disclosure Program (VDP) on the perception of taxpayers, and is moderated by government trust. The data collection technique used in this study is convenience sampling. This study used a sample of 115 respondents from KPP Pratama Surabaya Mulyorejo. The data used are primary data obtained through questionnaires and interviews with taxpayers. The data analysis technique used validity, reliability, classical assumptions and MRA (Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…The voluntary disclosure program can also reduce asymmetry information, indicating that agents benefit from taxes in economic activity. This research also supports previous research (Irawan & Raras, 2021), where there is an increase in taxpayer compliance with tax practices carried out due to the voluntary disclosure program as well as research supporting Ningtyas & Aisyaturrahmi (2022) who concluded that the voluntary disclosure program has a positive influence on taxpayer perceptions and strengthens the relationship between the Government and taxpayers.…”
Section: Resultssupporting
confidence: 88%
“…The voluntary disclosure program can also reduce asymmetry information, indicating that agents benefit from taxes in economic activity. This research also supports previous research (Irawan & Raras, 2021), where there is an increase in taxpayer compliance with tax practices carried out due to the voluntary disclosure program as well as research supporting Ningtyas & Aisyaturrahmi (2022) who concluded that the voluntary disclosure program has a positive influence on taxpayer perceptions and strengthens the relationship between the Government and taxpayers.…”
Section: Resultssupporting
confidence: 88%
“…Sanction is an action in the form of punishment given to someone who does not comply with the rules. Mardiasmo (2016) stated that taxation sanctions are the guarantee that the tax laws and regulations (taxation norms) will be obeyed. According to Yuniarwati and Widjaja (2019), there are two kinds of tax sanctions, which are administrative sanction and criminal sanction.…”
Section: Methodsmentioning
confidence: 99%
“…Program pengungkapan sukarela atau dikenal dengan tax amnesty jilid II merupakan kebijakan yang diperuntukkan bagi wajib pajak orang pribadi dan diharapkan menjadi program pengampunan pajak yang terakhir sehingga menimbulkan deterrent effect bagi wajib pajak (Hasanah, et al, 2021). Wajib pajak memiliki kecenderungan untuk berpartisipasi dalam program pengungkapan sukarela apabila memberikan keuntungan secara finansial (Ningtyas & Aisyaturrahmi, 2022).…”
Section: Pendahuluanunclassified